Use of Kahoot as a motivating element in the teaching-learning process - Rojas-Viteri, Juan (2021)
The present study arose from the need to generate in the investigated students the desire to learn while having fun. Active learning methodologies and, especially, gamification have been widely used nowadays; there is an endless number of digital tools on the web that fulfill this purpose. The general objective of the research was to analyze the use of Kahoot as a motivating element in the teaching-learning process. The methodology used in structuring this work was empirical-analytical and descriptive. In addition, quiz-type questionnaires were used throughout the 2019-2020 school year to reinforce the topics covered in each class, which made it possible to statistically measure the students' preference for the use of Kahoot. The population was determined by thirty-five students who belonged to the second semester of the Pedagogy of Experimental Sciences and Computer Science course at the Central University of Ecuador (UCE). The results revealed that the students investigated showed to be motivated at the moment of learning, as well as at the moment of being evaluated, since they felt no pressure to respond. Finally, it was demonstrated that Kahoot is a digital tool that motivates the teaching-learning process, encouraging students to attend classes and participate more actively in the classroom.